Pengaruh Karakteristik Komite Audit, Perusahaan dan Struktur Kepemilikan Terhadap Kecurangan Pelaporan Keuangan - Andrian Budi Prasetyo (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2016)
This study examines the effect of audit committee characteristics, firm characteristic and ownership structure on the likelihood of fraudulent financial reporting. Audit committee characteristics is examined by audit committee financial expertise, meetings of the audit committee and the audit committee tenure. Firm characteristic is examined by the leverage, firm size, firm’s growth rate and external auditor. Ownership structure is examined by managerial ownership and institutional ownership. This research is using a quantitative methods research. This research is using secondary data that comes from the cases list of Otoritas Jasa Keuangan (OJK) and annual reports of the listed companies on the Indonesia Stock Exchange (IDX). Using a sample of 15 fraud and 15 non-fraud firms, we did not find a significant relation between the independent variabels and fraudulent financial reporting.